2014
DOI: 10.1088/0004-637x/795/1/85
|View full text |Cite
|
Sign up to set email alerts
|

NEAR 3:2 AND 2:1 MEAN MOTION RESONANCE FORMATION IN THE SYSTEMS OBSERVED BYKEPLER

Abstract: The Kepler mission has released ∼ 4229 transiting planet candidates. There are approximately 222 candidate systems with three planets. Among them, the period ratios of planet pairs near 1.5 and 2.0 reveal that two peaks exist for which the proportions of the candidate systems are ∼ 7.0% and 18.0%, respectively. In this work, we study the formation of mean motion resonance (MMR) systems, particularly for the planetary configurations near 3:2 and 2:1 MMRs, and we concentrate on the interplay between the resonant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 48 publications
3
38
0
1
Order By: Relevance
“…However, as a comparison, if they are initially in a compact configuration, the probability of the forming planets in 2:1 MMRs will significantly decrease. As shown in the work of Wang & Ji (2014), they found that if the planets pairs were initially in compact configuration at the separations of ∼ 15 Hill radius, the probability of 2:1 MMRs decreased to 10% in 50 runs and there was no simulation that three planets were evolved into 4:2:1 MMRs. Secondly, in our simulations we slow down the speed of type I migration for low-mass planets, and this could further explain why two planets are fairly easier to be trapped into 2:1 MMRs.…”
Section: The Emergence Of 4:2:1 Mmrs Only With Terrestrial Planetsmentioning
confidence: 88%
“…However, as a comparison, if they are initially in a compact configuration, the probability of the forming planets in 2:1 MMRs will significantly decrease. As shown in the work of Wang & Ji (2014), they found that if the planets pairs were initially in compact configuration at the separations of ∼ 15 Hill radius, the probability of 2:1 MMRs decreased to 10% in 50 runs and there was no simulation that three planets were evolved into 4:2:1 MMRs. Secondly, in our simulations we slow down the speed of type I migration for low-mass planets, and this could further explain why two planets are fairly easier to be trapped into 2:1 MMRs.…”
Section: The Emergence Of 4:2:1 Mmrs Only With Terrestrial Planetsmentioning
confidence: 88%
“…The observed period ratios between adjacent pairs (Figure 1) show that most of the period ratios are smaller than three, and there is a pile-up of period ratios around the 3:2 and 2:1 mean motion resonances (MMRs). The existence of planet pairs near first-order MMRs is often ascribed to disk migration (Snellgrove et al 2001;Lee & Peale 2002;Lee & Thommes 2009;Wang & Ji 2014). However, we might expect the overabundance to be larger if disk migration is common, though Pan & Schlichting (2017) suggested that resonance zhoujl@nju.edu.cn † jason.steffen@unlv.edu 1 https://exoplanetarchive.ipac.caltech.edu capture is more difficult for smaller planets in a disk.…”
Section: Introductionmentioning
confidence: 99%
“…Convergent migration in protoplanetary discs is an effective and popular MMR formation mechanism (Snellgrove et al 2001), and can also achieve three-body resonances (Peale & Lee 2002;Libert & Tsiganis 2011), although some MMRs are harder to lock into than others (Rein et al 2012; Tadeu dos Santos et al 2015). Forming the 3:2 MMR in particular through energy dissipation has been widely investigated (Papaloizou & Szuszkiewicz 2005;Hadjidemetriou & Voyatzis 2010;Emel'yanenko 2012;Ogihara & Kobayashi 2013;Wang & Ji 2014;Zhang et al 2014). Capture into MMRs through gravitational scattering alone -after the dissipation of the protoplanetary disc -occurs relatively rarely (Raymond et al 2008).…”
Section: Introductionmentioning
confidence: 99%